Novel catalysts for dechlorination of polychlorinated biphenyls (PCBs) and other chlorinated aromatics. - Fletcher, A; Moss, J; Cowley, A; O'Hare, D (2007)
Diiron complexes of fluorene and fluorene* (1,2,3,4,5,6,7,8,9-nonamethylfluorene) have been found to be catalysts for the dechlorination of chlorinated aromatics, such as PCBs.